Influence of Crouch Angle on Postural Stability in Quiet Stance and Functional Tasks Among Children with Cerebral Palsy. - Shetty, Triveni; Mullerpatan, Rajani; Ganesan, Sailakshmi (Developmental Neurorehabilitation)
The aim of this study is to investigate postural stability and function (functional tasks) in younger (<12 yr) and older (>12 yr) children with lesser (<25°) and greater crouch (>25°) during stance. Postural stability and functional tasks were assessed in 53 ambulatory children with spastic cerebral palsy (CP). Younger and older children with greater crouch angle demonstrated higher displacement of center of pressure compared to children with lesser crouch angle during gait (p <.01). All (younger and older) children with severe crouch angle demonstrated strong association of postural control with stair climb (r = 0.732; p <.05) and timed-up-and-go test (r = 0.84; p <.01). Greater crouch angle demonstrates a moderate association with postural stability (r = 0.528; p <.01) in quiet stance and a strong association with functional tasks in children with CP (r = 0.7–0.84; p <.05).